Allogeneic blood transfusion and the prognosis of gastric cancer patients: Systematic review and meta-analysis. (January 2015) - Sun, Chang; Wang, Yi; Yao, Hou Shan; Hu, Zhi Qian
Abstract: Background : Perioperative allogeneic blood transfusion (ABT) may be a deleterious predictor on the prognosis of gastric cancer (GC) for subjects who had undergone curative surgeries. In this article we proposed to figure out the effect of ABT with a systematic review and meta-analysis.Methods : Relevant articles were identified by searching Pubmed and Embase to March 2014. A random-effects model or fixed-effects model was used to calculate pooled odds ratios (ORs). Sensitivity analysis, meta-regression, stratified analysis, dose–response meta-analysis were conducted, and publication bias tested.Results : Eighteen studies (9120 GC patients) were included, of which 36.3% received transfusions. ABT was associated with increased all-cause mortality (OR, 2.17; 95% confidence interval [CI], 1.72–2.74; p < 0.001; I 2 = 75%). Sensitivity analysis showed significant changes in ORs while meta-regression had little influence on ORs. Galbraith plot revealed the OR reduced to 2.10 (95% CI, 1.86–2.37; p < 0.001) with tau 2 reduced to 0.00 and I 2 reduced to 0%. Results of stratified analysis were robust and consistent. Dose–response meta-analysis revealed that all-cause mortality was significantly lower in patients transfused with ≤800 mL of blood than those transfused with >800 mL (OR, 0.58; 95% CI, 0.37–0.92; p = 0.02; I 2 = 54%). ABT was also associated with increased cancer-related mortality (OR, 2.57, p = 0.011) and recurrence (OR, 1.52, p = 0.017).Conclusions : In GC patients undergoing curative surgeries, ABTs are associated with a worse prognosis, including all-cause mortality, cancer-related mortality and recurrence. Patient blood management should be investigated further to minimize use of ABT. Highlights: Transfusion is associated with increased all-cause mortality. Dose-response relationship between transfusion and prognosis is found. Transfusion is associated with increased cancer-related mortality and recurrence.